1993
DOI: 10.1016/0735-1097(93)90327-w
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of right ventricular mass in normal subjects and in patients with primary pulmonary hypertension by nuclear magnetic resonance imaging

Abstract: Electrocardiogram-gated spin echo NMR imaging of the heart may be used for quantitating right ventricular mass in normal subjects and in patients with primary pulmonary hypertension, in whom it may also provide an alternative noninvasive technique for estimating mean pulmonary artery pressure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
3

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(83 citation statements)
references
References 21 publications
8
72
3
Order By: Relevance
“…Mean error for intraobserver and interobserver variability was 10.3% and 5.8%, respectively, for indexed RV EDV, and 11.8% and 5.7%, respectively, for indexed LV EDV (2). Mean intraobserver and interobserver variability for RV mass was 11.7 6 10.4% (r ¼ 0.99, standard error of estimate (SEE) ¼ 6.53 g) and 11.02 6 3.92% (r ¼ 0.99, SEE ¼ 7.86 g), respectively (32).…”
Section: Discussionmentioning
confidence: 95%
“…Mean error for intraobserver and interobserver variability was 10.3% and 5.8%, respectively, for indexed RV EDV, and 11.8% and 5.7%, respectively, for indexed LV EDV (2). Mean intraobserver and interobserver variability for RV mass was 11.7 6 10.4% (r ¼ 0.99, standard error of estimate (SEE) ¼ 6.53 g) and 11.02 6 3.92% (r ¼ 0.99, SEE ¼ 7.86 g), respectively (32).…”
Section: Discussionmentioning
confidence: 95%
“…Radionuclide angiography measures the right ventricular ejection fraction (RVEF) [79], as does MRI, considered to be the "gold-standard" for assessing right atrial and ventricular dimensions, ventricular mass, and ventricular wall motion [80][81][82][83][84][85]. One study has shown an association between lower baseline RVEF and an increased risk of death, independent of other factors [45].…”
Section: Other Cardiac Imaging Modalitiesmentioning
confidence: 99%
“…Impressive results for accuracy have been demonstrated by several investigators in various disease states [11][12][13][14][15]. The interstudy reproducibility of CMR-derived parameters of ventricular function and mass is good for both the left and right ventricles and is superior to two-dimensional and Mmode echocardiography [16][17][18].…”
Section: Cardiac Magnetic Resonance Imaging Introductionmentioning
confidence: 99%
“…2). Right ventricular hypertrophy is a consequence of the increased pulmonary afterload [13]. The left ventricular mass does not differ significantly from normal values in pulmonary hypertension patients [13].…”
Section: Ventricular Massmentioning
confidence: 99%